FORMULASI DAN UJI ANTIBAKTERI SEDIAAN SABUN CAIR EKSTRAK ETANOL DAUN JAMBU BIJI (Psidium guajava L) DENGAN BASIS MINYAK KELAPA TERHADAP BAKTERI Staphylococcus aureus - tohir, fauzha muftia; ahwan, ahwan; Qonitah, Fadilah (PC Ikatan Apoteker Indonesia (IAI) Karanganyar, 2025)
The use of extracts from medicinal plants in the community is used to prevent diseases, maintain body freshness and treat diseases. Guava leaves (Psidium guajava L) contain active compounds such as tannins, triterpenoids, flavonoids, saponins, alkaloids, and essential oils that have antibacterial effects. This study aims to determine the antibacterial activity of liquid soap ethanol extract of guava leaves against Staphylococcus aureus bacteria. The liquid soap formula of guava leaf extract (Psidium guajava L) is made into 4 formulas F0 (0%), F1(5%), F2(10%), and F3(15%). Antibacterial activity is seen from the antibacterial activity test using the diffusion method. Physical testing of guava leaf ethanol extract liquid soap includes organoleptic, pH, foam height, homogeneity, and viscosity. The results of the study showed that the entire formula qualified for good physical properties and could inhibit the growth of Staphylococcus aureus. The results of the antibacterial activity test showed that guava leaf extract soap (Psidium guajava L) had an inhibition in the formula F0 of 0.00±0.00 mm (no antibacterial activity), F1 of 4.60±0.46 mm (weak antibacterial activity), F2 of 5.27±0.06 mm (moderate antibacterial activity), F3 of 5.93±0.32 mm of moderate antibacterial activity) and a positive control of 11.77±1.46 mm (strong antibacterial activity). Based on the results of the study, it was concluded that the liquid soap formula of guava leaf extract (Psidium guajava L) has good physical properties and shows antibacterial activity against Staphylococcus aureus, and does not differ significantly (p<0.05).